The influence of the Role of Public Manager On the Satisfaction of the Nagari Community in West Sumatera / Dasman Lanin, S. Syamsir and Boni Saputra - Lanin, Dasman; S, Syamsir; Saputra, Boni (2021)
The fulfillment of public services or public goods is one of the important roles of local governments, including the lowest government called the village or other names such as Nagari. Since the issuance of Village Law Number 6 of 2014, where there are two important aspects of the role of the Village/Nagari government in governance, namely, community development and empowerment. The general manager is the village leadership which aims to run government, development, and community empowerment, where the results of the leadership activities can be in the form of policies, programs, and village government activities that provide outputs, benefits, and impacts for the community he leads. So it is necessary to study the extent of the role of public managers on the satisfaction of the people they lead (Irawan, 2017). The role of government leaders or public managers becomes crucial in times of uncertainty in people's lives, such as those experienced by society. Nagari in West Sumatra Province is interesting to be the object of research because the Nagari community in their affairs certainly needs their respective Nagari guardians. As a government agency that acts to provide services to the community, the role of public managers in villages in West Sumatra has a major problem in providing the services needed following the expectations of the community. Therefore, the problem is; Is there any influence of the role of public managers (interpersonal, informational, and decision-making), either partially or simultaneously on the satisfaction of the Nagari community in West Sumatra?